Wright of Derby : from the shadows / Christine Riding and Jon King. - Riding, Christine; King, Jon (National Gallery Global, 2025)
Renowned for his depictions of dramatic contrasts between darkness and light, Joseph Wright of Derby created a significant series of paintings 'by candlelight' between 1765 and 1773. Centred around masterpieces including 'An Experiment on a Bird in the Air Pump' from the National Gallery and 'A Philosopher Lecturing on the Orrery' from Derby Museum and Art Gallery, this publication explores the social and artistic context of these pictures, foregrounding them as outstanding examples of European painting. The candlelight scenes offer a wealth of insights into Wright's own thinking as well as contemporary preoccupations during the 'Age of Enlightenment', reflecting the artist's concerns with death, melancholy, scientific progress and scepticism. The publication also discusses aesthetic debates concerning the sublime, as well as childhood wonder, curiosity and the loss of innocence.